2021
DOI: 10.1111/acer.14575
|View full text |Cite
|
Sign up to set email alerts
|

Trends in US Alcohol Consumption Frequency During the First Wave of the SARS‐CoV‐2 Pandemic

Abstract: Background The SARS‐CoV‐2 pandemic created disruptions and stressors which may have influenced alcohol consumption frequency trends. Varying COVID‐19 health burden and alcohol policies may have contributed to different consumption trends between states. The aim of this study is to assess trends in alcohol consumption and moderation by state of residence. Methods We examined trends in adult drinking days, during the first wave of the pandemic (March 10 to June 8) using l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 64 publications
3
27
1
Order By: Relevance
“…High-risk drinking was associated with a sextupled odds of retrospectively-reported increased alcohol use compared with those reporting moderate or low-risk drinking, after adjusting for boredom and living with a partner. These findings are consistent with other studies conducted during the pandemic, which showed increased number of drinking days in March and April of 2020 ( McKetta et al, 2021 ; Capasso et al, 2021 ; Nordeck et al, 2021 ). This is concerning because high-risk drinking is associated with increased risk of adverse consequences including alcohol-related injuries, violence, and alcohol poisoning, and increased alcohol use could contribute to increased risk for alcohol-related problems ( Centers for Disease Control and Prevention, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…High-risk drinking was associated with a sextupled odds of retrospectively-reported increased alcohol use compared with those reporting moderate or low-risk drinking, after adjusting for boredom and living with a partner. These findings are consistent with other studies conducted during the pandemic, which showed increased number of drinking days in March and April of 2020 ( McKetta et al, 2021 ; Capasso et al, 2021 ; Nordeck et al, 2021 ). This is concerning because high-risk drinking is associated with increased risk of adverse consequences including alcohol-related injuries, violence, and alcohol poisoning, and increased alcohol use could contribute to increased risk for alcohol-related problems ( Centers for Disease Control and Prevention, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Risk for heavy drinking and AUD may be increased by stress from the social and economic circumstances brought about by the COVID-19 pandemic. Research from early in the pandemic has shown an increase in number of drinking days compared to the same time period in the previous year ( McKetta et al, 2021 ; Capasso et al, 2021 ; Nordeck et al, 2021 ), but the impact of mental health and economic stressors on drinking, particularly high-risk drinking, have not been widely assessed. Research from previous epidemics suggests that negative mental health consequences of quarantine—including distress, irritability, depression, post-traumatic stress symptoms, and problematic alcohol use—may be long-lasting, enduring after the public health risk has abated ( Brooks et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, suicidal ideation was predicted by greater alcohol intake in combination with financial worries. This is particularly concerning, as recent evidence suggests that alcohol purchases, consumption, and dependence behaviors increased dramatically for those under lockdown during the first 6-months of the pandemic (39,48,49). For those at risk of suicidal ideation, alcohol intake should be minimized/avoided (5).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of US adults have found significant increases in the frequency of alcohol consumption [ 18 ], including binge drinking [ 19 ]. Moreover, although some have found evidence of an association between COVID‐19‐related stress and increased drinking behaviors [ 20 ], others have found increases in drinking behavior among individuals living in states with relatively lower COVID‐19 disease burden [ 21 ], suggesting alcohol use may be sensitive to contextual and psychosocial factors. Finally, there have been increases in alcohol retail sales because many states closed bars/restaurants and relaxed alcohol sale restrictions by allowing curbside distribution or delivery.…”
Section: Introductionmentioning
confidence: 99%